2010
DOI: 10.1891/1559-4343.12.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Self-Harm and Medicine’s Moral Code: A Historical Perspective, 1950–2000

Abstract: “Deliberate self-harm”— acts of self-poisoning (overdosing) or self-injury (e.g., cutting) that do not result in death — has historically provoked a moral judgment in those professionals who treat it. Such judgments negatively value the act of self-harm and lead to the discriminatory treatment of self-harmers in accident and emergency departments and upon psychiatric wards. This article argues that the treatment of self-harmers in such environments has its origins in a “moral code” that negatively values the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…These included the 10 main scales used in Knutson's analyses, the three additional scales found in Knutson et al but not used in their analyses, as well as three new scales: self-harm; regularity of the actor's actions (Bonce vs. repeated event^); and likelihood that the participant would have acted differently than the actor in the vignette (Bact differently^) ( Table 1). The latter scales were included in our study to broaden the assessment of event features implicated in MJ (Cresswell & Karimova, 2010;Reynolds & Ceranic, 2007;Phillips et al, 2015), but were only peripheral to our main goal.…”
Section: Vignette Subsetsmentioning
confidence: 99%
“…These included the 10 main scales used in Knutson's analyses, the three additional scales found in Knutson et al but not used in their analyses, as well as three new scales: self-harm; regularity of the actor's actions (Bonce vs. repeated event^); and likelihood that the participant would have acted differently than the actor in the vignette (Bact differently^) ( Table 1). The latter scales were included in our study to broaden the assessment of event features implicated in MJ (Cresswell & Karimova, 2010;Reynolds & Ceranic, 2007;Phillips et al, 2015), but were only peripheral to our main goal.…”
Section: Vignette Subsetsmentioning
confidence: 99%
“…Also from Durkheim (1992), the theory adopts a morally relativistic approach to social deviance: human behaviours classified as deviant elicit various labels ranging from immorality to criminality to mental illness. Selfharm is an apt example of relativistic moral classification in that until the Suicide Act of 1961,which decriminalised suicide in England and Wales, it was classified as a criminal offence, having being interpreted during the previous historical era as 'attempted suicide' (see Cresswell and Karimova, 2010;Millard, 2015). Since then it has been re-classified as a behaviour appropriately addressed via health-based interventions such as NICE clinical guidelines (2004,2011) and suicide prevention programmes (HM Government, 2012).…”
Section: Moral Code Theorymentioning
confidence: 99%
“…This binary coding remains relevant today. In terms of EDs it has been usefully historicized in the work of Cresswell and Karimova (2010) and Millard (2015). This research emphasised that self-harm's binary code both pre-dates and post-dates Jeffrey's ethnography and indicated that the contemporary moral code of self-harm in EDs should be dated from the Suicide Act of 1961, which both decriminalised non-fatal self-harm and then re-institutionalised it within a health-based rather than crime-based system of values.…”
Section: The Moral Code In Emergency Departments (Eds)mentioning
confidence: 99%
“…What separated the self-harmer in A&E as nowhere else within the psycomplex was the in situ comparison with two other 'emergency' groups: (1) the accident-victim; (2) the 'genuinely' ill, none of whom inflicted 'deliberate' self-harm (Cresswell and Karimova 2010). Thus, an iatrogenic vocabulary swung into view -the selfharmer was 'manipulative', 'attention-seeking', 'irresponsible' (Cresswell and Karimova 2010;Pembroke 1994) vis-à-vis the other two groups -and this iatrogenesis became not only registered in the experience of self-harmers but, for the first time from 1989 onwards, problematized as a manifestation of power 2 within the psy-complex. The politics of self-harm was 'born'.…”
Section: Smos and Interconnected Networkmentioning
confidence: 99%
“…Self-harm is 'a deliberate non-fatal act, whether physical, drug overdosage or poisoning, done in the knowledge that it was potentially harmful, and in the case of drug overdosage, that the amount taken was excessive' (Morgan 1979, 88). The connection of self-harm to completed suicide has long been researched (Cresswell and Karimova 2010). Until 1961 it was legally classified as 'attempted suicide' and a criminal offence that could be punished by imprisonment.…”
Section: Introductionmentioning
confidence: 99%